Structural Equation Model for Investigating Risk Factors Affecting Project Success in Surabaya. (2015) - Chandra, Herry Pintardi
Abstract: A great deal of literature has pointed to the importance of understanding the construction project risk. Risks inherent in every construction project that can affect of project success. Risk is present in all situations that can be identified such as natural risks, design risks, resources risks, financial risks, legal and regulatory risks, and construction risks. The objectives of this paper are to identify the factors that causes of risks, to identify the factors of project success, and to represent the model of risk factors that affecting the project success. The data collected from the questionnaire survey carried out to 180 valid responses were analyzed with the assistance of structural equation modeling (SEM) to predict the project success. The results of the structural equation modeling suggest that the relationship between risk factors and project success in Surabaya projects can be explained by standardized coefficient of 0.442 for natural risks; -0, 499 for design risks; 0, 257 for resources risks; 0.651 for financial risks; 0.166 for legal and regulation risks; and -0.197 for construction risks. Project success is significantly related to cost (standardized coefficient of 0.878), quality (standardized coefficient of 0.873), time (standardized coefficient of 0.804), customer satisfaction (standardized coefficient of 0.884), and profit (standardized coefficient of 0.850). In order to achieve project success, suggestions are made for preparing financial risks related to inflation rate.